UPAYA PENINGKATAN KREATIVITAS SENI RUPA SISWA MELALUI TEKNIK PENCETAKAN DENGAN BANTUAN MEDIA ASLI - Ardita Destiani; Sri Saparahayuningsih; Wembrayarli Wembrayarli (Jurnal Ilmiah POTENSIA, 2016)
The problem this research is whether through printing technique assisted by original media can improve students B1 group art creativity?. The purpose of this research is to improve art creativity through printing technique assisted by original media. Method of this research to be Classroom Action Research with subject of research children B1 group at Early Chilhood Education Aisyiah Bustanul Athfal II Bengkulu City, that of 11 peoples, 8 boys and 3 girls . Data was collected by observation. Data analyzed by mean evaluation formula and mastery learning formula. The results of this research indicate that through printing technique assisted by original media can increases children’s art creativity with results of mean value good, whereas children’s achieved mastery learning is 81,8%. From results of this research can recomended to early chilhood education teachers for improving children's creativity can use learning through art activity with printing technique by original media.